Pengaruh Brand Image Terhadap Proses Keputusan Pembelian Sepatu Nike (Studi Pada Mahasiswa Fakultas Komunikasi dan Bisnis Telkom University Bandung) - Dwi Ajeng Wulandari; Farah Oktafani (Jurnal Computech & Bisnis (e-Journal), 2017)
In modern times, developments in the world of fashion is growing by leaps and bounds. One of the highly developed is the trend of shoes. Sales of Nike shoes increases every year, as a result many companies that want to take advantage by selling shoes that quality is not in accordance with company standards. This study aimed to analyze the effect of Brand Image tehadap Nike Shoes Purchase Decision Process (Studies in the Faculty of Communication and Business Student Telkom University Bandung). This research includes quantitative research. The method used is descriptive - causal. The population in this study were students of the Faculty of Communication and Business Telkom University who uses Nike shoes. The sampling technique used is nonprobability sampling with the sampling method incidental sampling. The data collection is done by distributing questionnaires to 100 respondents. Data analysis technique used is simple linear regression analysis. Based on the results, it can be concluded that Brand Image positively influence the purchase decision process Nikes on students of the Faculty of Communication and Business Telkom University Bandung. It can be seen from the results of the t> t table (12.257> 1.98447) and the level of significance, 000 <0.05. Based on the calculation coefficient of determination (R2) can be seen the influence of brand image variable (X) on the purchase decision process (Y) amounted to 60.5%. While the remaining 39.5% is influenced by other factors  Keywords: brand image, buying decision process, consumer behavior